Bacteriological Etiology of Flood Affected Diarrhoeal Patients Admitted in Dhaka Medical College Hospital and Antibiogram of the isolates - Rahman, Abdur; Rashid, Aliya; Begum, Shaheen Ara; Chowdhury, Aktheruzzaman; Begum, Shahin Ara; Shahid, Sazzad Bin (Bangladesh Journal of Medical Microbiology, 2016)
Diarrhoea is a self-limiting disease caused by various enteropathogens and antimicrobial therapy is an important adjunct to fluid therapy in the management of the cases. We have studied the flood-affected diarrhoeal (post-flood diarrhoea) patients admitted in Dhaka Medical College Hospital during August to September, 2007. A total of ll4 faecal samples were collected from the patients of all age groups, and investigated for bacterial enteropathogens. Specimens were cultured in appropriate media and identification of the organisms showing growth was done by relevant biochemical tests. In addition, the isolates of Vbrio cholera wer confirmed using pollvalent antisera. Sensitivity of the isolated organisms was done by disc diffusion method. Among the isolated bacterial enteropathogens, majority was V. cholera (46, 40.3%). Other isolates included Escherichia coli (18, 23.0%), Aeromonas species (8,10.O%) and V parahaemolyticus (5, 7.0%). No pathogenic bacteria were isolated from 27 of the cases. No Salmonella or Shigella was detected in any case. Majority of the cases (24, 52.0%) infected with V cholerae were children having less than L0 years of age. Most of the isolates of V cholerae (77.7%) were sensitive to Ciprofloxacin. Almost all of the V cholerae isolates (97.90 ) were resistant to Tetracycline, followed by Co-trimoxazloe (93,5%) and Nalidixic acid (59.2%). All of the E. coli isolates (100.0%) were sensitive to Ceftriaxone, followed by Ceftazidime (88.8%) and Ciprofloxacin (77.7oh). Thus it can be concluded that Ciprofloxacin and Ceftriaxone can be considered as the drugs ofchoice for the treatment of post-flood diarrhoea along with proper rehydration therapy. Bangladesh J Med Microbiol2008; 02 (01):13-17 DOI: http://dx.doi.org/10.3329/bjmm.v8i1.21929